2‐Fluorodeschloroketamine has similar abuse potential as ketamine. (27th March 2022) - Li, Feng; Du, Han; Wu, Bo; Wei, Jiayun; Qiao, Yanling; Lai, Miaojun; Zhou, Wenhua; Shen, Haowei; Wang, Youmei; Xu, Peng; Di, Bin
Abstract: 2‐Fluorodeschloroketamine (2‐FDCK) as a substitute for ketamine has emerged among drug abusers in recent years. However, 2‐FDCK has not been controlled or regulated in many countries, which may be partly related to the lack of evidence on its abuse potential. In this study, we evaluated the abuse potential of 2‐FDCK via the tests of the conditioned place preference (CPP), locomotor sensitization, drug self‐administration and drug discrimination using ketamine as a reference. 2‐FDCK induced significant CPP at a minimum dose of 3 mg/kg in mice, an effect comparable with that of ketamine (3 mg/kg). Acute injections of 2‐FDCK or ketamine at 30 mg/kg enhanced locomotor activity. Repeated treatments with this dose of 2‐FDCK and ketamine induced locomotor sensitization after withdrawal. 2‐FDCK readily induced self‐administration with 0.5 mg/kg/infusion, the same dose for ketamine, and induced the highest seeking response at 1 mg/kg. Drug discrimination test showed that 2‐FDCK dose‐dependently substitute for ketamine with comparable ED50 to ketamine in substitution testing. Taken together, these results strongly suggested that 2‐FDCK has an abuse potential comparable with ketamine. Abstract : 2‐Fluorodeschloroketamine has not been controlled or regulated in many countries, which may be partly related to the lack of evidence on its abuse potential. The present study strongly demonstrated the rewarding, psychomotor, reinforcing, and stimulus effects of 2‐FDCK and strongly suggested that 2‐FDCK has an abuse potential comparable with ketamine.